The Role Of Government Expenditure, Investment And Exchange In Affecting Economic Growth In Indonesia - Elvira Ika Rosiana; Lorentino Togar Laut (Jurnal Ekonomi-Qu, 2022)
One of the benchmarks for the progress or failure of a country's economy is economicgrowth as seen from the value of its gross domestic product. This study aims to analyze the effect of Government Expenditure, Investment and Exchange Rate on Indonesia's Economic Growth in 1990 - 2020. The data used is secondary data using the Error Correction Model (ECM) analysis method. The findings in this study are the variables of Government Expenditure and Investment have a significant positive effect on economic growth in the long term, while in the short term it has no significant effect. The exchange rate variable in the long term and short term has a significant but negative effect on economic growth in Indonesia.